2015
DOI: 10.1016/j.jco.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

A Koksma–Hlawka inequality for general discrepancy systems

Abstract: a b s t r a c tMotivated by recent ideas of Harman (Unif. Distrib. Theory, 2010) we develop a new concept of variation of multivariate functions on a compact Hausdorff space with respect to a collection D of subsets. We prove a general version of the Koksma-Hlawka theorem that holds for this notion of variation and discrepancy with respect to D. As special cases, we obtain Koksma-Hlawka inequalities for classical notions, such as extreme or isotropic discrepancy. For extreme discrepancy, our result coincides w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
(31 reference statements)
0
23
0
Order By: Relevance
“…In the following, we recall the notion of variation introduced in [20]. Let D denote an arbitrary family of measurable subsets of…”
Section: D-variationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, we recall the notion of variation introduced in [20]. Let D denote an arbitrary family of measurable subsets of…”
Section: D-variationmentioning
confidence: 99%
“…
The recently introduced concept of D-variation unifies previous concepts of variation of multivariate functions. In this paper, we give an affirmative answer to the open question from [20] whether every function of bounded Hardy-Krause variation is Borel measurable and has bounded D-variation. Moreover, we show that the space of functions of bounded D-variation can be turned into a commutative Banach algebra.
…”
mentioning
confidence: 96%
“…Pausinger & Svane [25] have shown that twice continuously differentiable functions f admit finite V K (f ), and in addition they gave a bound which will be usefull in our context.…”
Section: Introductionmentioning
confidence: 96%
“…In the remaining part of the introduction we briefly sketch a more general concept of multidimensional variation which was recently developed in [25]. Let D denote an arbitrary family of measurable subsets of [0, 1] s which contains the empty set ∅ and [0, 1] s .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation